Short-chain fatty acid derivatives induce fetal globin expression and erythropoiesis in vivo - Pace, Betty S. (Blood, 2002)
Orally bioactive compounds that induce γ globin gene expression at tolerable doses are needed for optimal treatment of the β-hemoglobinopathies. Short-chain fatty acids (SCFAs) of 2 to 6 carbons in length induce γ globin expression in animal models, and butyrate, phenylbutyrate, and valproate induce γ globin in human patients. The usefulness of these compounds, however, is limited by requirements for large doses because of their rapid metabolism and their tendency to inhibit cell proliferation, which limits the pool of erythroid progenitors in which γ globin can be induced. Selected short-chain fatty acid derivatives (SCFADs) were recently found to induce γ globin and to stimulate the proliferation of hematopoietic cells in vitro. These SCFADs are now evaluated in vivo in nonanemic transgenic mice containing the human β globin gene locus and in anemic phlebotomized baboons. In mice treated with a SCFAD once daily for 5 days, γ globin mRNA increased 2-fold, reticulocytes increased 3- to 7-fold, and hematocrit levels increased by 27%. Administration of 3 SCFADs in anemic baboons increased F-reticulocytes 2- to 15-fold over baseline and increased total hemoglobin levels by 1 to 2 g/dL per week despite ongoing significant daily phlebotomy. Pharmacokinetic studies demonstrated 90% oral bioavailability of 2 SCFADs, and targeted plasma levels were maintained for several hours after single oral doses equivalent to 10% to 20% of doses required for butyrate. These findings identify SCFADs that stimulate γ globin gene expression and erythropoiesis in vivo, activities that are synergistically beneficial for treatment of the β hemoglobinopathies and useful for the oral treatment of other anemias.